Disasters and Trauma, That Are Harmful to Children and Adolescents, Are All Too Common in the Real World and the Digital World - Chung, Un Sun (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2024)
[...]it is crucial to develop effective strategies to prevent and address trauma, which can vary depending on a child’s age and developmental stage of the child [6]. [...]young individuals may experience long-lasting consequences in their future and develop pessimistic views of themselves, their environment, and what lies ahead [9]. [...]a nation facing historical trauma and social disasters should prioritize the mental well-being of children and teenagers. [...]professionals in the field of child and adolescent mental health must be knowledgeable about the various types of cyber violence, their characteristics, negative impacts, and strategies to combat them.